Human papillomavirus status and p16INK4A expression in patients with mucosal squamous cell carcinoma of the head and neck in Queensland, Australia. Issue 2 (April 2015) - Antonsson, Annika; Neale, Rachel E.; Boros, Samuel; Lampe, Guy; Coman, William B.; Pryor, David I.; Porceddu, Sandro V.; Whiteman, David C.
Highlights HPV prevalence in Australian HNSCCs and HPV affected cell-cycle regulation. Gender and alcohol consumption not associated with HPV or p16 status. Predictors of HPV-positivity were younger age (<60 years) and non-moderate smoking. High concordance between HPV/p16 status with a kappa of 0.72. Despite high concordance, we found 11% being discordant for HPV/p16 status.